Applications of Chinese Camellia oleifera and its By-Products: A Review - Quan, Wenxuan; Wang, Anping; Gao, Chao; Li, Chaochan (Frontiers in Chemistry, 2022)
Camellia oleifera is a woody oil tree species unique to China that has been cultivated and used in China for more than 2,300 years. Most biological research on C. oleifera in recent years has focused on the development of new varieties and breeding. Novel genomic information has been generated for C. oleifera, including a high-quality reference genome at the chromosome level. Camellia seeds are used to process high-quality edible oil; they are also often used in medicine, health foods, and daily chemical products and have shown promise for the treatment and prevention of diseases. C. oleifera by-products, such as camellia seed cake, saponin, and fruit shell are widely used in the daily chemical, dyeing, papermaking, chemical fibre, textile, and pesticide industries. C. oleifera shell can also be used to prepare activated carbon electrodes, which have high electrochemical performance when used as the negative electrode of lithium-ion batteries. C. oleifera is an economically valuable plant with diverse uses, and accelerating the utilization of its by-products will greatly enhance its industrial value.